Perbandingan Hasil Pengobatan Kasus Karsinoma Nasofaring Sebelum dan Selama Pandemi COVID-19: Pengalaman dari RSUD Dr. Soetomo pada 2017-2022 - Pratama, Mulia; Romdhoni, Achmad Chusnu; Dewanti, Linda (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2025)
Nasopharyngeal carcinoma is endemic in Southeast Asia. In Indonesia, the recorded mean prevalence is 6.2/100.000, with 13.000 yearly new Nasopharyngeal carcinoma cases. Observational data suggest that cancer-specific mortality was higher during the COVID-19 pandemic when compared with pre-pandemic levels. This study aims to compare the treatment outcome of nasopharyngeal carcinoma cases before and during the COVID-19 pandemic at Dr Soetomo Hospital in 2017-2022. This study employed a retrospective cross-sectional approach with an observational analytic method. Data is taken secondary from medical records for nasopharyngeal carcinoma patients at Dr. Soetomo Hospital in Surabaya and primary by telephone interview for additional information on the patient’s risk factors. The majority of nasopharyngeal carcinoma patients at Dr. Soetomo Hospital were male, elderly,>50 years old, and referral patients (outside Surabaya). In both eras, patients arrived already in stage 4 (advanced stage). However, before COVID-19, more patients were cured and survived before the COVID-19 period in comparison to during the COVID-19 pandemic period. This may be related to delayed treatment caused by COVID-19 policy on social distancing, healthcare regulation during the pandemic, and immunocompromised status.